sinx*cosx=1/2,(sinx)^3+(cosx)^3=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 21:15:21
sinx*cosx=1/2,(sinx)^3+(cosx)^3=?sinx*cosx=1/2,(sinx)^3+(cosx)^3=?sinx*cosx=1/2,(sinx)^3+(cosx)^3=?s
sinx*cosx=1/2,(sinx)^3+(cosx)^3=?
sinx*cosx=1/2,(sinx)^3+(cosx)^3=?
sinx*cosx=1/2,(sinx)^3+(cosx)^3=?
sinxcosx=1/2.===>2sinxcosx=1.===>sin(2x)=1.===>2x=2kπ+(π/2).===>x=kπ+(π/4).(一)当k为偶数时,k=2m.===>x=2mπ+(π/4).===>sinx=cosx=√2/2.===>sin³x+cos³x=2sin³x=√2/2.(二)当k为奇数时,k=2n+1.x=2nπ+π+(π/4).===>sinx=cosx=-√2/2.===>sin³x+cos³x=2sin³x=-√2/2.综上可知sin³x+cos³x=±√2/2.
2^3/2-3/2*2^1/2
(sinx)^3+(cosx)^3=(sinx+cosx)*((sinx)^2-sinxcosx+(cosx)^2)=(sinx+cosx)/2
((sinx)^3+(cosx)^3)^2=((sinx+cosx)/2)^2=(1+2sinxcosx)/4=1/2
(sinx)^3+(cosx)^3=√2/2
求证:(1+sinx+cosx)/(1+sinx-cosx)-(1+sinx-cosx)/(1+sinx+cosx)=2/tanx
证明:2(cosx-sinx)/1+sinx+cosx=cosx/1+sinx-sinx/1+cosx
证明:【2(cosx-sinx)】/(1+sinx+cosx)=cosx/(1+sinx) -sinx/(1+cosx)
求证cosX/(1+sinx)-sinx/(1+cosx)=2(cosx-sinx)/(1+sinx+cosx)
求证:2(sinx-cosx)/(1+sinx+cosx)=sinx/(1+cosx)-cosx/(1+sinx)
求证:cosx/1+sinx-sinx/1+cosx=2(cosx-sinx)/1+sinx+cosx
证明:2(cosx-sinx)/1+sinx+cosx=cosx/1+sinx-sinx/1+cosx
求证.[(1+sinx+cosx+2sinx cosx)/(1+sinx+cosx)]=sinx+cosx
证明2(cosx-sinx)/(1+sinx+cosx)=cosx/(1+sinx)-sinx/(1+cos)
已知tanx=2,计算(1)、2cosx-3sinx/sinx+cosx.(2)、sinx+cosx-sinx
y=sinx*sinx+2sinx*cosx
已知tanx=2,求(sinx*sinx+sinx*cosx)/(sinx*sinx+1)
cosx/1+sinx=-2则sinx-1/cosx=?
sinx*cosx=1/2,(sinx)^3+(cosx)^3=?
1-cosx +sinx/1+cosx+sinx=-2,tanx
求证:[(1-2sinxcosx)/sinx-cosx ]+cosx=sinx
若sinx*cosx=1/2,求tanx+cosx/sinx
(sinx+cosx)/(2sinx-cosx)=